Muhammadiyah’s Islamic philosophy in shaping the experiences of international students (a case study of the international students at the University of Muhammadiyah Malang) - Ifashabayo, Benjamin; Sukmana, Oman; Asrul, Nona Masnawati (Trigin Publisher, 2025)
This study explores the role of Muhammadiyah's Islamic philosophy in shaping the experiences of international students at the University of Muhammadiyah Malang (UMM). This topic needs to be studied because shaping the experiences of international students at Muhammadiyah’s universities supports the internationalization of Muhammadiyah’s higher institutions, especially UMM. As one of Indonesia's largest Islamic organizations, Muhammadiyah integrates the principles of Da’wah (Islamic propagation) and Tajdid (reform) into its educational framework, promoting inclusivity and cultural exchange. The study used a qualitative research method, the UMM students from 6 countries and UMM staff were interviewed. Data were collected through interviews, Observation, documents, and literature study. Thematic analysis was used for data analysis. The study examines how these principles influence international students' academic, social, and cultural lives. Findings reveal that Muhammadiyah's emphasis on interfaith dialogue and reform fosters a welcoming and harmonious environment, enabling students to navigate cultural and religious diversity effectively. However, challenges such as cultural adaptation and differing expectations highlight the need for enhanced support systems. This research underscores the significance of Islamic philosophy in global education and offers insights for institutions aiming to balance tradition with inclusivity in multicultural settings.